Organisational and methodological grounds for using functional stress tests in non-invasive assessment of endothelium-dependent reactions among persons with arterial hypertension risk factors - A. E. Skvortsov; M. Yu. Smirnova; I. G. Shchelkunova; A. V. Grechko (Российский кардиологический журнал)
.